The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1002/jbt.21816
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Carvacrol on Cisplatin-Induced Reproductive Damage in Male Rats

Abstract: Cisplatin (CP) treatment causes the damage in male reproductive system. Carvacrol (CARV) is an antioxidant that is naturally found in some plants. We aimed to investigate the effect of CARV on CP-induced reproductive toxicity in male rats. Eighteen adult male Sprague-Dawley rats were used. The control group (n = 6) was treated orally with physiological saline (PS) daily for 14 days and a single intraperitoneal (IP) PS injection on day 10. The CP group (n = 6) was administered with daily oral PS for 14 days and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 30 publications
(44 reference statements)
4
42
0
1
Order By: Relevance
“…Oxidative stress occurs due to excessive increase in reactive oxygen species depending on the deterioration of oxidant–antioxidant balance in the body (Ak & Gulcin, ; Aksu et al, ; Bursal & Gülçin, ; Gulcin, ). Due to oxidative stress, damage occurs in lipids, proteins and DNA, which are the macromolecules that make up the cell; that is why, cell integrity is impaired (Aksu et al, ). In the studies on mice and monkeys, methyl mercury has been reported to reduce sperm count and motility (Mohamed, Burbacher, & Mottet, ; Rao, ).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress occurs due to excessive increase in reactive oxygen species depending on the deterioration of oxidant–antioxidant balance in the body (Ak & Gulcin, ; Aksu et al, ; Bursal & Gülçin, ; Gulcin, ). Due to oxidative stress, damage occurs in lipids, proteins and DNA, which are the macromolecules that make up the cell; that is why, cell integrity is impaired (Aksu et al, ). In the studies on mice and monkeys, methyl mercury has been reported to reduce sperm count and motility (Mohamed, Burbacher, & Mottet, ; Rao, ).…”
Section: Introductionmentioning
confidence: 99%
“…A rich composition of polyunsaturated fatty acids in the mammalian sperm cell membrane makes the cell sensitive to free radicals. There are many experimental studies reporting that increased ROS levels decrease sperm motility and quality and increase the rate of sperm death in the semen . Using antioxidant compounds may be a useful and important strategy for preventing male infertility caused by chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have examined the adverse effects of CP on sperm quality and reproductive organ weights (Aksu et al, , ; Saral et al, ). Aksu et al () demonstrated that CP administration resulted in a decrease in total testicular weight, sperm motility and sperm concentration and an increase in abnormal sperm rates as compared to these parameters in a control group.…”
Section: Discussionmentioning
confidence: 99%
“…The average of the values from these observations was used as the final motility score (Aksu et al, ). To determine the percentage of morphological sperm abnormalities, the method of Aksu et al () was used. Briefly, slides were prepared by staining each semen sample with eosin–nigrosin dye.…”
Section: Methodsmentioning
confidence: 99%